Electrophosphorescence: Very High Efficiency Orange‐Red Light‐Emitting Devices with Low Roll‐Off at High Luminance Based on an Ideal Host–Guest System Consisting of Two Novel Phosphorescent Iridium Complexes with Bipolar Transport (Adv. Funct. Mater. 47/2014). (December 2014) - Li, Guomeng; Zhu, Dongxia; Peng, Tai; Liu, Yu; Wang, Yue; Bryce, Martin R.
<x xml:space="preserve">Abstract</x> An all‐phosphor host‐guest doping system is presented by Y. Liu, Y. Wang, M. R. Bryce, and colleagues on page 7420. It is based on two novel Ir complexes possessing bipolar transporting ability and realizes ultra‐high efficiency orange‐red phosphorescent organic light‐emitting devices, which exhibit constant peak power efficiency of >75 lm W−1 and external quantum efficiency of >26% as well as extremely low efficiency roll‐off within a certain range of 8 and 15 wt%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>